Intervenção humanitária no contexto migratório venezuelano : ações do ACNUR e da OIM no Estado de Roraima - Albuquerque, Élysson Bruno Fontenele de (2021)
From the migratory movement that took place in the Bolivarian Republic of Venezuela, around 2015, there was a process of exodus of Venezuelans towards other countries, resulting in a constant and intense circulation of the population in Latin America and the Caribbean. In this context, as of 2016, it reverberated in Brazil with the significant entry of the Venezuelan population by the state of Roraima, the United Nations High Commissioner for Refugees (UNHCR) and the International Organization for Migration (IOM), leading agencies on the theme of refugees and migrants, interested in seeking durable solutions, started their humanitarian intervention actions, which later, together with the State's action, with the creation of Operação Acolhida, consolidated operations in the response of reception and reception to Venezuelans in Roraima, through the establishment of the Civil-Military relationship. The research aims to analyze the actions of the leading agencies, UNHCR and IOM, based on the scenario developed for humanitarian intervention in the state of Roraima after the federalization of the response. Through the methodological procedures established for the research, it begins with a bibliographic and documentary review, in primary and secondary sources regarding the performance of the UN agencies in the migratory context, from the materialization of the humanitarian intervention, in addition to the analysis, the insertion of the researcher in the scope of the response helps to observe the procedures developed to establish the reception and insertion of the Venezuelan population to the receiving State, since the reality of the state of Roraima is a matter of concern because it is a state located in a region of difficult access, and with little contact with the rest of the country, in the midst of a period of marked migratory movement, it became visible to its fragility due to the lack of an efficient service system with the intensification of the displaced Venezuelan population and the omission of efficient migration policies that aim to establish strategies to welcome migrants and refugees that enter the Brazilian State.